Correlation between Intensive Training Program (ITP) and English and Arabic Proficiency Test (EAPT) results: An analysis of three language skills of postgraduate students - Mariana, Ana; Hula, Ibnu Rawandhy N.; Husain, Dahlia; Pakaya, Nurul Aini (Universitas Islam Sultan Agung, 2025)
This study measures the correlation between the Intensive Training Program (ITP) and the English and Arabic Proficiency Test (EAPT) scores among 100 postgraduate students at IAIN Sultan Amai Gorontalo from four non-language programs. A quantitative method with an ex-post facto design was used, and data analysis was conducted using Spearman’s correlation test. Data were collected through a three-aspect proficiency test: listening (istima’), structure (tarakib), and reading (qira’ah), using a Computer Assisted Test (CAT) application with 140 items. The test results were processed using score conversion and SPSS Version 30. Before the ITP, none of the students achieved the minimum passing score for the EPT (450), and only six passed the APT. After the training, 18% reached the minimum EPT score, and the number of students who passed the APT increased significantly to 32. Correlation analysis showed that ITP effectively improved listening (correlation 0.582; p=0.002) and structure (correlation 0.592; p=0.002) in EPT, but was less effective for reading (correlation 0.085; p=0.686). In contrast, ITP greatly enhanced all aspects of APT: istima’ (correlation 0.972; p=0.000), tarakib (correlation 0.993; p=0.000), and qira’ah (correlation 0.997; p=0.000). The short duration of the training affects its effectiveness, along with students’ educational backgrounds and learning motivation. To enhance efficacy, it is recommended to extend the training duration, provide relevant modules for non-language students, enhance motivation through regular practice, and improve reading instruction methods. ITP positively impacts Arabic and English language proficiency, particularly for APT, suggesting that targeted training can significantly benefit non-language students’ language skills.